2022
DOI: 10.2147/ptt.s372262
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Guselkumab for Moderate to Severe Psoriasis: A 3-Year Real-Life Retrospective Study

Abstract: Introduction Guselkumab safety and efficacy profiles in psoriasis have been showed by VOYAGE (1 and 2) trials. Although trial results have been already previously confirmed by real-life studies, long-term real-life data, and drug survival data about guselkumab are still poor. Patients and Methods We performed a 3-year retrospective study, with the aim of assessing guselkumab efficacy and safety profile in the management of plaque psoriasis in a real-life setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…This is close to the results by Megna et al. (PASI 90 in 77.4% and PASI 100 in 54.8%, after 120 weeks) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is close to the results by Megna et al. (PASI 90 in 77.4% and PASI 100 in 54.8%, after 120 weeks) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Real-world evidence for mean PASI score with a treatment duration of about 3 years is available only from Megna et al. (120 weeks) with a slightly worse result (mean PASI 1.0) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown the efficacy and safety of guselkumab for PsO treatment in a real world setting. Benhadou et al 27 reported the efficacy and safety in the short term, while Megna et al 28 reported the long‐term benefit of guselkumab after 3 years of therapy. Moreover, the German registry PERSIST confirmed the efficacy and safety in the short and the long term 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The advent of biologic agents over nearly two decades has dramatically enhanced the treatment of moderate to severe psoriasis. Data from randomized controlled trials (RCTs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] have demonstrated that these agents can be highly efficacious. Yet the preponderance of evidence has been garnered from studies that have primarily included White patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, while prior real-world evidence (RWE) studies have demonstrated the effectiveness of biologic therapies for psoriasis [4][5][6][7][8][9][10][11][12][13][14][15][16], there is little published data comparing the efficacy of biologics in Asian compared with other ethnicities in RWE studies. Real-world evidence is essential for providing insight into the efficacy and safety of drug treatments across all patients with psoriasis since the typical strict inclusion criteria of RCTs often exclude many patient populations seen in routine clinical care, including those with multiple comorbidities, ethnic and racial subpopulations, older adults, and patients for whom multiple biologics have failed.…”
Section: Introductionmentioning
confidence: 99%